Ageing, Popular Culture and Contemporary Feminism
X, 254 p.
Keywords: How has popular film, television and fiction responded to the realities of an ageing Western population? This volume analyses this field of representation to argue that, while celebrations of ageing as an inspirational journey are increasing, most depictions still focus on decline and deterioration.